Development of Milk Processing Business Based on Blue Economy in Mundu Klaten - Handayani, Selfiya Sri; Rini, Ayu Dwidyah; Purwandaya, Budhi (Universitas Ciputra Surabaya, 2022)
The dairy business of Ngudi Mulyo's Women's Livestock Group (KWT) in Mundu Village has the potential of dairy cow's milk resources, but the business is not developing well. Thus, the objectives of this study are: 1.) Implementation of the Blue Economy principle in the KWT dairy business, 2.) the interrelationships between economic, social, and environmental elements of the KWT dairy business, 3.) Analyzing the form of the KWT milk processing business strategy. This study uses a mixed methods approach, and uses primary and secondary data, and uses NVIVO software to analyze content and Stata as a quantitative data processing tool. The results of the analysis show that the processing business of Ngudi Mulyo's KWT cow's milk has absorbed labor, production waste and resources can still be utilized. An environmentally friendly business development strategy, product marketing development and improvement and partner cooperation are needed for business continuity.